Meningkatkan Kreativitas Anak Pada Materi Seni Rupa Melalui Teknik Montase Di Tk Putri Ananda Kecamatan Poasia Kota Kendari - Rosnawati Rosnawati; Aris Suziman; Chairan Zibar L. Parisu (Prodi PGSD Unsultra, 2020)
The purposes of this study were to increase children’s creativity in fine arts material through the use of montage technique at TK Putri Ananda, increase teacher’s instructional effectiveness in teaching fine arts material through the use of montage technique at TK Putri Ananda, and to increase children’s learning activities in fine arts material through the use of montage technique at TK Putri Ananda.Results of the study showed that, after conducting treatments in two cycles with four meetings to remedy learning, it was found that the use of montage technique could increase the children’s creativity, as indicated by results of evaluation using an assessment guideline (BSB + BSH), which was 68.75% in cycle I and 87.5 in cycle II. These results suggested that the children’s creativity at TK Putri Ananda has increased as a result of using montage technique in the teaching of fine arts material. The study was concluded after cycle II since the minimum target of learning completeness set by the school, which was 85%, had been met. In terms of the learning completeness, the implementation of lesson scenario by the teacher reached 90%, which meant that it had been well done. Finally, the children’s activities in their learning of montage successfully increased to 87.5%. Keywords: Creativity, Fine Arts, Montage